Augmented reality advertising and college students' interest in the extreme sports: Moderating role of innovation resistance and health consciousness - Zhang, Shaoqiong; He, Ningning (Frontiers in Public Health, 2022)
Advertising and promotions are the most utilized types of augmented reality (AR) activations for marketers across all industries. The same is true for the sports industry. This form of augmented reality is meant to bring attention to the organization through a novel technology such as AR. Recently, a lack of interest among students in extreme sports has been attributed to a lack of professional advertising and marketing innovation. This situation requires the attention of researchers, and this study investigates the impact of augmented reality advertising on college students' interest in extreme sports, specifically in China. The article also investigates the moderating role of innovation resistance and health consciousness in the relationship between augmented reality advertising and college students' interest in extreme sports in China. Students actively participating in sports were selected using the purposive sampling technique, and AMOS was used for data analysis. According to the findings, augmented reality advertising positively correlates with interest in extreme sports. The findings also revealed that innovation resistance and health consciousness significantly moderated college students' interest in extreme sports and augmented reality advertising. This research assists regulators in developing regulations to increase interest in extreme sports through augmented reality advertising and innovation adoption.